Murine Ileocolic Bowel Resection with Primary Anastomosis - Perry, Troy (J Vis Exp, 2014)
Intestinal resections are frequently required for treatment of diseases involving the gastrointestinal tract, with Crohn’s disease and colon cancer being two common examples. Despite the frequency of these procedures, a significant knowledge gap remains in describing the inherent effects of intestinal resection on host physiology and disease pathophysiology. This article provides detailed instructions for an ileocolic resection with primary end-to-end anastomosis in mice, as well as essential aspects of peri-operative care to maximize post-operative success. When followed closely, this procedure yields a 95% long-term survival rate, no failure to thrive, and minimizes post-operative complications of bowel obstruction and anastomotic leak. The technical challenges of performing the procedure in mice are a barrier to its wide spread use in research. The skills described in this article can be acquired without previous surgical experience. Once mastered, the murine ileocolic resection procedure will provide a reproducible tool for studying the effects of intestinal resection in models of human disease.